1985
DOI: 10.2307/1941302
|View full text |Cite
|
Sign up to set email alerts
|

Niche Separation of Two Damselfish Species by Aggression and Differential Microhabitat Utilization

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on TueAbstract. Two herbivorous, interspecifically territorial West Indian damselfishes, the beaugregory (Eupomacentrus leucostictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 30 publications
1
71
1
Order By: Relevance
“…It appears that the avoidance of aggression from the dominant P. amboinensis either forces the subordinate P. moluccensis into a more vulnerable location, or distracts them and thereby lowers their vigilance to nearby predators. Competitive dominance can shift among species depending on habitat characteristics in damselfishes [25], but the present study highlights that this will not always be the case. It also highlights that interference competition can have a major indirect effect on mortality through habitat-related behavioural modification.…”
Section: Discussionmentioning
confidence: 61%
“…It appears that the avoidance of aggression from the dominant P. amboinensis either forces the subordinate P. moluccensis into a more vulnerable location, or distracts them and thereby lowers their vigilance to nearby predators. Competitive dominance can shift among species depending on habitat characteristics in damselfishes [25], but the present study highlights that this will not always be the case. It also highlights that interference competition can have a major indirect effect on mortality through habitat-related behavioural modification.…”
Section: Discussionmentioning
confidence: 61%
“…Despite often strong interspecific competition, a number of studies have failed to demonstrate any effect of 1 competing species on the growth and mortality of another (Doherty 1982, Robertson 1984, Roberts 1987, Jones 1988, 1991. However, a number of studies have shown that interspecific pat-terns of resource use can be influenced by competition (Ebersole 1985, Robertson & Gaines 1986, and in 1 study a long-term effect of one species on the abund.ance of another c0mpetin.g species has been demonstrated (Robertson 1996). Therefore, although there has been considerable speculation that competition is important in the ecology of tropical reef fishes, it has not been widely demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Interspecific competition that is highly asymmetrical has been shown to influence the distribution of coral-reef fishes among microhabitats (e.g. Ebersole 1985, Robertson & Gaines 1986, Clarke 1989, Munday et al 2001, McCormick & Weaver 2012. At a similar scale (within local populations), I have demonstrated that competition that is symmetrical between species can also determine the distribution of juvenile coral-reef fishes.…”
Section: Discussionmentioning
confidence: 77%